2014
DOI: 10.1016/j.brainres.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine decreases inhibitory but not excitatory neurotransmission to cardiac vagal neurons in the nucleus ambiguus

Abstract: Dexmedetomidine, an α2 adrenergic agonist, is a useful sedative but can also cause significant bradycardia. This decrease in heart rate may be due to decreased central sympathetic output as well as increased parasympathetic output from brainstem cardiac vagal neurons. In this study, using whole cell voltage clamp methodology, the actions of dexmedetomidine on excitatory glutamatergic and inhibitory GABAergic and glycinergic neurotransmission to parasympathetic cardiac vagal neurons in the rat nucleus ambiguus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
(16 reference statements)
2
21
0
3
Order By: Relevance
“…-receptor agonists inhibit both sEPSCs and sIPSCs (Bateman, Boychuk et al 2012), and 1 receptors inhibit IPSCs (Boychuk, Bateman et al 2011). The 2 receptor agonist clonidine and dexmedetomidine inhibit sIPSC (Philbin, Bateman et al 2010;Sharp, Wang et al 2014). Finally, photostimulation of endogenous adrenergic fibers from locus coeruleus inhibited NAm neuronal discharge by selective augmentation of inhibitory currents (Wang, Pinol et al 2014).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…-receptor agonists inhibit both sEPSCs and sIPSCs (Bateman, Boychuk et al 2012), and 1 receptors inhibit IPSCs (Boychuk, Bateman et al 2011). The 2 receptor agonist clonidine and dexmedetomidine inhibit sIPSC (Philbin, Bateman et al 2010;Sharp, Wang et al 2014). Finally, photostimulation of endogenous adrenergic fibers from locus coeruleus inhibited NAm neuronal discharge by selective augmentation of inhibitory currents (Wang, Pinol et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Adrenergic signaling plays an important role in central autonomic control of NAm cholinergic output by modulating excitatory and inhibitory synaptic transmission, as shown by subtype selective adrenoceptor agonists/antagonists (Philbin, Bateman et al 2010;Boychuk, Bateman et al 2011;Bateman, Boychuk et al 2012;Sharp, Wang et al 2014).…”
Section: 1 and  Receptor Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sharp et al, using a whole-cell voltage clamp methodology, showed that dexmedetomidine decreased both GA-BAergic and glycinergic inhibitory input to cardiac vagal neurons but had no significant effect on excitatory input in the rat nucleus ambiguus. 10) This means that decreasing inhibitory neurotransmission to cardiac vagal neurons increases the excitability of parasympathetic neurons, leading in turn to bradycardia. Thus, atropine, as an anticholinergic drug, is effective for the bradycardia induced by dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%